PENGGUNAN INTERNET DAN PERUBAHAN NORMA KEWARGANEGARAAN DALAM ERA TRANSISI KE DEMOKRASI DI INDONESIA - RASUL, NAJMUDDIN MOHAMMAD (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2014)
The purpose of this study is to determine whether internet use correlate to change of citizenship norms in the context of Indonesia's transition to democracy. The main theoretical framework is media and social change. For data gathering, 384 young voters between the ages of 17 to 40 years were interviewed in Padang, West Sumatra, Indonesia. The results of the srudy show that internet use has a significant correlation with citizenship norms (compliance, duty, and engaged citizenship). Based on the findings it can be concluded that the political euphoria in the era of transition to democracy has changed pattern of media usage and citizenship norms among the young generation in Indonesia.